Kidney transplantation in Kazakhstan: the burden of organ shortage - S. A. Abdugafarov; M. N. Assykbayev; D. J. Saparbay (Вестник трансплантологии и искусственных органов, 2021)
Kidney transplantation has been the best replacement therapy for end-stage kidney disease for over 60 years. The Republican Coordination Center for Transplantation reports that as of January 29, 2020, there were 2675 people on the kidney transplant waiting list in the Republic of Kazakhstan. The issue of deceased donation in Kazakhstan is problematic for various reasons. Over the past couple of years, the already low rates of deceased donors have fallen by more than 2 times.Objective: to objectively assess the effectiveness of deceased-donor kidney transplant in order to indicate the need for development of cadaveric donation and reduce the number of patients in the transplant waitlist.Materials and methods. Fifty-two kidney transplants from a deceased donor were performed at the National Research Oncology Center (NROC) from 2010 to 2020. The age group of recipients ranged from 20 to 75 years old. In most cases, end-stage chronic renal failure resulted in chronic glomerulonephritis (76%), pyelonephritis (1.9%), polycystic kidney disease (9.6%) and diabetic nephropathy (11.5%).Results. The 1-year and 5-year survival rates were 96% and 86%, respectively. There was delayed graft function in 13 of cases. In one case (1.92%), there was intraoperative hyperacute rejection of the kidney transplant that could not be treated with high doses of glucocorticosteroids; the kidney graft was removed. Two patients (3.8%) in the early postoperative period, on days 2 and 7 after surgery, developed a clinic of acute renal transplant rejection; after the rejection crisis was stopped by drug therapy, graft function was restored. One patient (1.92%) died as a result of bilateral pneumonia, which led to sepsis and death.Conclusion. Graft and recipient survival rates after deceased-donor kidney are comparable to those after living-donor kidney transplantation. The solution to the problems of increasing the number of deceased organ transplants should not rest entirely on the shoulders of transplant doctors; this task must also be addressed at the government level with constant propaganda to explain to the citizens the need for a deceased organ donation program.